Psychological resilience and its relationship to learned helplessness among a Sample of University Students in Idlib Governorate (The International Journal for Scientific Research, 2025)
The current study aims to reveal the level of both psychological resilience and learned helplessness and the relationship between them in a sample of university youth in Idlib Governorate, and whether there are differences in these variables attributed to the variable of gender. The descriptive approach was used in this study, and the final sample amounted to (232) including (109) male students and (123) female students. The researcher used the Conner and Davidson Psychological Resilience Scale (CD-RISC) and the Quinless and Nelson learned Helplessness Scale (LHS). The results showed that the level of psychological resilience is average and the level of learned helplessness is high, and that the relationship is inverse between the two variables, meaning that the higher one of the variables increases, the lower the other, and the differences in psychological resilience were attributed to the gender variable in favor of females, while there were no differences in learned helplessness attributed to the gender variable.
Keywords: Psychological Resilience; Learned Helplessness